The malaria parasite PP1 phosphatase controls the initiation of the egress pathway of asexual blood-stages by regulating the rounding-up of the vacuole. - Marie Seveno; Manon N Loubens; Laurence Berry; Arnault Graindorge; Maryse Lebrun; Catherine Lavazec; Mauld H Lamarque (PLoS Pathogens)
A sustained blood-stage infection of the human malaria parasite P. falciparum relies on the active exit of merozoites from their host erythrocytes. During this process, named egress, the infected red blood cell undergoes sequential morphological events: the rounding-up of the surrounding parasitophorous vacuole, the disruption of the vacuole membrane and finally the rupture of the red blood cell membrane. These events are coordinated by two intracellular second messengers, cGMP and calcium ions (Ca2+), that control the activation of their dedicated kinases, PKG and CDPKs respectively, and thus the secretion of parasitic factors that assist membranes rupture. We had previously identified the serine-threonine phosphatase PP1 as an essential enzyme required for the rupture of the surrounding vacuole. Here, we address its precise positioning and function within the egress signaling pathway by combining chemical genetics and live-microscopy. Fluorescent reporters of the parasitophorous vacuole morphology were expressed in the conditional PfPP1-iKO line which allowed to monitor the kinetics of natural and induced egress, as well as the rescue capacity of known egress inducers. Our results underscore a dual function for PP1 in the egress cascade. First, we provide further evidence that PP1 controls the homeostasis of the second messenger cGMP by modulating the basal activity of guanylyl cyclase alpha and consequently the PKG-dependent downstream Ca2+ signaling. Second, we demonstrate that PP1 also regulates the rounding-up of the parasitophorous vacuole, as this step is almost completely abolished in PfPP1-null schizonts. Strikingly, our data show that rounding-up is the step triggered by egress inducers, and support its reliance on Ca2+, as the calcium ionophore A23187 bypasses the egress defect of PfPP1-null schizonts, restores proper egress kinetics and promotes the initiation of the rounding-up step. Therefore, this study places the phosphatase PP1 upstream of the cGMP-PKG signaling pathway, and sheds new light on the regulation of rounding-up, the first step in P. falciparum blood stage egress cascade.